Systematic Review of ERP-Driven Operational Transformation in Insurance, Utilities, and Critical Infrastructure Organizations - Oyinomomo-emi Emmanuel Akpe; Jeffrey Chidera Ogeawuchi; Abraham Ayodeji Abayomi; Oluwademilade Aderemi Agboola (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This paper presents a systematic review of ERP-driven operational transformation across the insurance, utilities, and critical infrastructure sectors. As organizations in these highly regulated industries face increasing pressure to enhance operational efficiency, compliance, and service delivery, Enterprise Resource Planning (ERP) systems have emerged as critical tools for integration and process optimization. This review synthesizes the role of ERP systems in addressing sector-specific needs, such as regulatory compliance, risk management, and operational agility, while also discussing the challenges associated with their implementation, including system integration, user resistance, and data migration issues. Key success factors for ERP adoption, such as clear leadership, robust change management, and continuous training, are highlighted alongside case study examples of successful and unsuccessful implementations. Additionally, the paper explores future research directions, focusing on the impact of emerging technologies like AI, the integration of sustainability initiatives, and sector-specific ERP customizations. By examining these critical aspects, this paper offers valuable insights for industry leaders, policymakers, and IT decision-makers to optimize ERP adoption and drive operational transformation in the insurance, utilities, and critical infrastructure sectors.